Ta có: x = \(\frac{7^{16}-3}{7^{16}+1}=\frac{7^{16}+1-4}{7^{16}+1}=1-\frac{4}{7^{16}+1}\)
y = \(\frac{7^{17}-3}{7^{17}+1}=\frac{7^{17}+1-4}{7^{17}+1}=1-\frac{4}{7^{17}+1}\)
Do \(7^{16}+1< 7^{17}+1\) => \(\frac{4}{7^{16}+1}>\frac{4}{7^{17}+1}\) => \(-\frac{4}{7^{16}+1}< -\frac{4}{7^{17}+1}\)
=> \(1-\frac{4}{7^{16}+1}< 1-\frac{4}{7^{17}+1}\) => x < y
Trả lời:
\(x=\frac{7^{16}-3}{7^{16}+1}=\frac{7^{16}+1-4}{7^{16}+1}=\frac{7^{16}+1}{7^{16}+1}-\frac{4}{7^{16}+1}=1-\frac{4}{7^{16}+1}\)
\(y=\frac{7^{17}-3}{7^{17}+1}=\frac{7^{17}+1-4}{7^{17}+1}=\frac{7^{17}+1}{7^{17}+1}-\frac{4}{7^{17}+1}=1-\frac{4}{7^{17}+1}\)
Ta có: \(7^{16}< 7^{17}\)
\(\Leftrightarrow7^{16}+1< 7^{17}+1\)
\(\Leftrightarrow\frac{4}{7^{16}+1}>\frac{4}{7^{17}+1}\)
\(\Leftrightarrow-\frac{4}{7^{16}+1}< -\frac{4}{7^{17}+1}\)
\(\Leftrightarrow1-\frac{4}{7^{16}+1}< 1-\frac{4}{7^{17}+1}\)
\(\Leftrightarrow x< y\)
Vậy x < y